1994
DOI: 10.1016/0378-1097(94)90444-8
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and analysis of the gene in Borrelia burgdorferi encoding the immunogenic P39 antigen

Abstract: The P39 antigen is a specific, highly conserved, and immunogenic protein of Lyme disease spirochetes, Borrelia burgdorferi sensu lato. The nucleotide sequence of the gene encoding this protein was determined and found to be the first of two tandemly arranged open reading frames located on the spirochete's chromosome. These two open reading frames were designated bmpA for the gene encoding P39 and bmpB for the gene encoding the putative protein ORF2 encoded by the second open reading frame. The nucleic acid seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
55
0
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 23 publications
8
55
0
1
Order By: Relevance
“…On the basis of their estimated sizes, the 5Ј ends of the cleaved RNA species map to the vicinity of the putative promoter within the 5Ј region of bmpA (43) Table 1). The 5Ј end of the primer-extended products for bmpAB mapped to an A at Ϫ32 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of their estimated sizes, the 5Ј ends of the cleaved RNA species map to the vicinity of the putative promoter within the 5Ј region of bmpA (43) Table 1). The 5Ј end of the primer-extended products for bmpAB mapped to an A at Ϫ32 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding genes are confined to a single locus on the linear chromosome of this organism in the following 5Ј33Ј gene order: bmpD-bmpC-bmpA-bmpB (2,15,33,43). The paralogs share a high degree of homology at both the DNA (56 to 64%) and protein (36 to 46% identity) levels (2,15,33,37,43). Although the function of none of these proteins has been established, the conservation of their genes within the B. burgdorferi sensu lato complex (2,16,33,37,43) and the presence of orthologs in Treponema pallidum (41) and numerous other bacteria (B. burgdorferi genome web site at the Institute for Genomic Research) suggest that these proteins fulfill an essential physiological role.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…From the sequenced borrelial genome, three σ factor homologs were identified: rpoD (σ 70 ), ntrA (σ 54 ), and rpoS (σ S ) (Fraser et al, 1997). Borrelial promoters for genes encoding Osps (Howe et al, 1986;Jianhui et al, 1997), flagellin (Ge et al, 1997), and p39 antigen (Simpson et al, 1994) were identified by their homology to consensus sequences in E. coli. As expected, the predominant σ factor appears to be σ 70 -like.…”
Section: B Organization Of Borrelial Promotersmentioning
confidence: 99%